Over-reaction and under-reaction in climate policy: an institutional analysis - Peters, B. Guy; Jordan, Andrew J.; Tosun, Jale (Journal of environmental policy and planning, 2017)
In what circumstances do organizations react to changes in their operating environment by adopting proportionate policy responses? And drawing on institutional theory, what expectations can we formulate in relation to the proportionality of policy responses to climate change? These two research questions frame this article, which seeks to make new connections between the emerging perspective of proportionality in policy-making and existing institutional theories. We find that institutional theories are well suited to formulating expectations concerning the (dis)proportionality of policy responses, but their explanatory power can be further improved by taking the characteristics of specific climate policy problems into account. While there are many different problems nested in the ‘meta’ problem of climate change, we find that most of them have characteristics which suggest that policy under-reactions are more, not less likely. Amongst institutional theories, rational choice institutionalism provides the clearest expectation that proportionate policy responses are unlikely. Policy entrepreneurship is identified as one obvious way in which to stimulate proportionate policy responses, through fostering new ways of thinking within organizations.